Focal encyclopedia of electronic media (Butterworth- Heinemann, 1998)
The Focal Encyclopedia of Electronic Media (FEEM) is an up-to-date, authoritative, and comprehensive reference source. Directed to applications of electronic media technology, it clearly explains technologies and methods to those seeking to use them, in both industry and academia. Entry emphasis is on clear language, illustrations, organization, and ease of use. Applications, processes, definitions, and use of equipment are described in detail. This information is important for creative personnel, technical professionals, management decision-makers, corporate media users and directors, and anyone seeking background on applications of and trends in media equipment and processes.